2020
DOI: 10.3389/fonc.2020.587666
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Biliary Tract Cancer in Patients With Type 2 Diabetes

Abstract: Aim: This retrospective cohort study evaluated whether metformin use in patients with type 2 diabetes mellitus might reduce the risk of biliary tract cancer (BTC); and explored whether metformin use might affect the overall survival in patients who developed BTC. Methods: New-onset type 2 diabetes patients aged 25-75 years during 1999-2005 were enrolled from the Taiwan's National Health Insurance and followed up until December 31, 2011. A total of 287,995 ever users and 16,229 never users were identified (unma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…68 Furthermore, a retrospective study by Tseng et al, demonstrated that metformin significantly decreases the risk of biliary tract cancer by 50%-60%, although it does not affect OS in these patients. 69 Accordingly, Yang et al reported that metformin does not improve survival in patients with CCA and diabetes. 70 Thus, in light of this still controversial evidence, inhibition of OXPHOS in cancer cells as an approach to counteract CCA progression deserves further investigation.…”
Section: Cca and Glucose Metabolismmentioning
confidence: 99%
“…68 Furthermore, a retrospective study by Tseng et al, demonstrated that metformin significantly decreases the risk of biliary tract cancer by 50%-60%, although it does not affect OS in these patients. 69 Accordingly, Yang et al reported that metformin does not improve survival in patients with CCA and diabetes. 70 Thus, in light of this still controversial evidence, inhibition of OXPHOS in cancer cells as an approach to counteract CCA progression deserves further investigation.…”
Section: Cca and Glucose Metabolismmentioning
confidence: 99%
“…The aim was clear in all the studies analyzed. As the four selected studies were retrospective (one case–control study [32], one cohort study [31], and two population-based data studies [33,34]), any of the studies were judged to apply the most appropriate recruitment strategy to explore the aim. The study design and the qualitative methodology were judged appropriate in all but one paper [33], in which considerable biases could be held-up by the creation of a simulated control population and by the discrepancy between the groups as regards potential risk factors for CCA other than diabetes and metformin intake.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the anatomical location of CCA, one study [31] considered both intrahepatic and extrahepatic forms, whereas another study investigated GBC carcinoma, intrahepatic and extrahepatic CCA [34], another [32] considered only the intrahepatic type, whereas for the fourth study [33], no information was provided regarding the anatomical classification. However, we considered for the analysis only intrahepatic CCA and possibly perihilar CCA, excluding distal CCA, GBC, and AVCs.…”
Section: Resultsmentioning
confidence: 99%
“…Second, our previous observational studies conducted in patients with type 2 diabetes mellitus in Taiwan by using the nationwide NHI database suggest that metformin use is associated with a lower risk of various types of cancer, including lung cancer [24], colorectal cancer [25,27], breast cancer [37], thyroid cancer [38], bladder cancer [39], prostate cancer [40], endometrial cancer [41], ovarian cancer [42], cervical cancer [43], kidney cancer [44], oral cancer [45], gastric cancer [46], esophageal cancer [47], nasopharyngeal cancer [48], skin cancer [49], pancreatic cancer [50], hepatocellular cancer [51], biliary tract cancer [52], non-Hodgkin's lymphoma [53], and bone cancer [54]. These findings suggest that the anti-cancer effects of metformin may involve some common pathophysiological pathways in cancer development, probably targeting many of the hallmarks of cancer [55].…”
Section: Discussionmentioning
confidence: 99%